Prevalence of sleep disturbance and its associated factors among diabetes type-2 patients in Saudi Arabia - Al-Qahtani, Faisal Saeed (Frontiers in Public Health, 2024)
This study investigated the prevalence of sleep disturbances among people living with type 2 diabetes in Saudi Arabia. A four-stage sampling method was used to recruit 479 participants from various parts of the country. A self-administered questionnaire was used to collect demographic, sleep disruption, and related clinical characteristics. Data analysis included reporting sleep disturbance prevalence as frequency and percentage, chi-square tests to examine categorical variable associations, and multiple logistic regression analysis to identify independent factors associated with sleep disturbances. Results showed that most participants were male (59.3%), married (78.5%), and university-educatedDiploma/Bachelor's degree holders (41.5%). The study found that most respondents had subjective sleep quality issues, with 55.3% of Sleep Latency participants having trouble falling asleep, 62.4% having trouble sleeping, 65.1% experiencing serious sleep efficiency impairment, 85.2% reporting sleep difficulties, 88.5% using sleep medication without difficulty, 5.4% having moderate difficulty, and 6.1% having considerable difficulties. The Global Pittsburgh Sleep Quality Index (PSQI) showed that all participants had sleep problems. Marital status, nationality, HBA1C, education, region, comorbidity, and monthly income were significantly associated with sleep disturbance characteristics. The study also concluded that diabetes itself can increase the risk of sleep problems, as it is associated with various sleep-related issues such as insomnia, sleep apnea, and restless legs syndrome.Encouraging social support within the realm of healthcare services holds significance in reducing the occurrence of inadequate sleep. For individuals diagnosed with type 2 diabetes mellitus, managing their blood sugar levels effectively is crucial for enhancing the quality of their sleep. Furthermore, engaging in regular physical activity is essential for preventing subpar sleep quality.